SEJARAH BANGUNAN SHOWROOM FUCHS & RENS YOGYAKARTA ABAD XX-XXI MASEHI - Supriyanto, Mahathelge Ahmad (Historia, 2025)
The beginning of the 20th century was a period of development of automobile transportation in the Dutch East Indies. The presence of cars in the Dutch Indies was the result of the efforts of car importers. On Jalan Pangeran Mangkubumi Yogyakarta, there is a colonial style building which is currently a souvenir shop. Initially the building was a showroom for the Fuchs & Rens company. This building needs to be researched because there is no study regarding this colonial building, so discussion regarding this colonial building is very important to find out detailed information regarding this building. The research methods were literature study, observation, architectural analysis, stylistic analysis and then continued with morphological analysis to obtain research results. In this research, we found that the colonial building, about which no information is known, was a branch of the Fuchs & Rens showroom. Apart from that, the extensive transformation of the Fuchs & Rens building was also found in this research